Toward effective communication of agrometeorological services - T. Cegnar; H. Boogaard; K. Finkele; B. Lalic; J. Raymond; S. Lifka; D. M. Schultz; V. Tarchiani (Advances in Science and Research, 2023)
Agrometeorological services are a subset of climate services targeted to support farmers' tactical and strategic decisions, with the potential to support farmers' capacity to cope with climate variability and change, as well as strengthen their resilience toward climatic risks. However, the effectiveness of such services is often limited by inadequate and unsuitable means of communication with farmers. Therefore, in recent years, the World Meteorological Organization (WMO) and partners have focussed their efforts on improving communication through these services. At the European Meteorological Society (EMS) Annual Meeting in September 2022, a workshop on effective communication of agrometeorological services was held as a hybrid side event, with the aim of answering the question: “How can we deliver efficient and effective agrometeorological services”? The workshop was a joint endeavour of Met Éireann, the International Society of Biometeorology, the EMS Media and Communication Committee, the Slovenian Environment Agency, the Slovenian Meteorological Society, and the S. W. Tromp Foundation. The aim of this workshop was to advance better communication of services to the agriculture sector as a basis for promoting adaptive strategies for weather and climate change, which would enable sufficient food production at present and in the future. The workshop also provided an opportunity for transdisciplinary discussions between national meteorological and hydrological services, universities, research institutes, private companies, and the WMO. The topics discussed at the workshop included learning about exemplar agrometeorological services at various national hydrometeorological services, strengthening communication of agrometeorological services to end-users, improving data and information sharing, and educating end-users. The workshop resulted in a list of recommendations for the future.